Erratum: Siddagangaiah, S., Chen, C.-F., Hu, W.-C., Pieretti, N. A Complexity-Entropy Based Approach for the Detection of Fish Choruses. Entropy 2019, 21(10), 977 - Shashidhar Siddagangaiah; Chi-Fang Chen; Wei-Chun Hu; Nadia Pieretti (Entropy, 2019)
We have found an error in the order of one author’s name and surname in the article recently published in Entropy [1]: Shashidhar Siddagangaiah 1,*, Chi-Fang Chen 1,*, Wei-Chun Hu 1 and Pieretti Nadia 2 that should be corrected to the following order in this paper [1]: Shashidhar Siddagangaiah 1,*, Chi-Fang Chen 1,*, Wei-Chun Hu 1 and Nadia Pieretti 2 [...]